Strategic Synergy of Digitality, Spirituality, and Prosocial Leadership in Strengthening MSME Resilience in Jakarta - Rajwa Ganendra; Jacquelinda Sandra Sembel (Universitas Pelita Harapan, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a critical role in Jakarta’s urban economy, yet they face increasing pressure to remain resilient, surviving digital disruption, economic volatility, and post-pandemic recovery. This study investigates the interconnected influence of Digital Mastery, Prosocial Leadership, and Islamic Spirituality on Business Resilience among MSMEs in Jakarta. Drawing on Resilience Theory, the research proposes a holistic framework that integrates technological competence, ethical leadership, and faith-based values as strategic assets for MSME sustainability. Using a quantitative approach and a descriptive correlation method, data was collected from 100 MSME respondents through structured survey questionnaires delivered online. The statistical analysis was conducted using SmartPLS4, assessing both the outer and inner models. Results reveal that Digital Mastery and Prosocial Leadership significantly influence Business Resilience, while Spirituality contributes indirectly through its influence on leadership and digital adoption. The model demonstrated strong explanatory power (R² = 0.707) and predictive relevance (Q² = 0.477), with Digital Mastery showing the largest effect size (F² = 0.915). This study offers theoretical contributions by extending Resilience Theory into a culturally grounded MSME context and practical implications for policymakers and educators seeking to empower small businesses through integrated digital, ethical, and spiritual development. The findings highlight the importance of holistic capacity-building strategies to foster resilient entrepreneurial ecosystems in emerging countries in Southeast Asia, with the case study in Indonesia.